Penanganan Tindak Pidana Anak oleh Kepolisian melalui Diversi sebagai Perlindungan Hak Anak - Yoserwan Yoserwan (Faculty of Law, Andalas University, 2019)
In the consideration of Law No. 23 of 2003 regarding Child Protection, it is stipulated that a child is bud, potential and young generation who will become the successor for aspiration of nation struggling and hold strategic value in securing the existence of this nation in the future. That why this law obligates the state and government to provide special protection for child in any condition. In Law No. 11 of 2012 regarding Juvenile Criminal Justice System, the protection is given by establishing special court for children who are committing a crime, which is separated from adult court. This law also mandates as a mandatory that the law enforcement agencies in each stage of criminal justice should apply diversion in solving any child crime or child in conflicting with law. For the police, which stand in the first row of criminal justice system, diversion process is actually can be applied by some procedures available. Those procedures are through the implementation of police discretion, penal mediation, and restorative justice or by solving trough adat law process. The implementation of those procedures in one hand will provide strong protection for child’s rights and on the other hand will secure the best interest of child.